Pb ANDCdCONTENTIN (Osphronemus gouramyand Channa micropeltes) FROM THE KOTO PANJANG DAM, RIAU PROVINSI - Suhaili Akbar; Budijono Budijono; M. Hasbi M. Hasbi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2020)
ABSTRACT            Osphronemus gouramy and Channa micropeltesinhabit the the Koto Panjang Dam, Riau. The presence of anthropogenic activities may produce heavy metal that enter the water and thus accumulate in the organisms living in that area. A study aims to understand the heavy metal content in gill, muscle and kidney of O. gouramy and C. micropeltesliving in that dam, as well as in the water and in the sediment has been conducted in April 2019. Samplings were conducted 2 times, once/ 2 weeks. Results shown that  the heavy metal content in O. gouramywere as follows: Pb 0.0873 mg/kg and Cd 0.0426 mg/kg (gill), Pb 0.0684 mg/kg and Cd 0.0394 mg/kg (kidney), Pb  0.0376 mg/kg and Cd 0.0219 mg/kg (muscle). Water quality parameters were as follows: pH 6-6.7, temperature 28-33°C, DO5.42-7.14, brightness 1.5-2.5 m and depth 22-55 m. Based on data obtained, it can be concluded that the heavy metals content in fish, in the water and sediment were relatively low. Key words: Koto Panjang Reservoir, heavy metal, goramy fish